Numerical Study on the Effect of Structural Parameters on the Behavior of BRBF-E - Bernardo A. Lejano; Michael Jayson S. Mas (Institut Teknologi Sepuluh Nopember, 2017)
Ductile braced frames are often used to resist lateral earthquake loads in steel buildings. However, the presence of the brace element can interfere with architectural features. Buckling-restrained braced frame in eccentric configuration (BRBF-E) is believed to have combined good performance in resisting earthquake loads and great flexibility for architectural design. Eccentrically braced frames can accommodate architectural openings for doors, windows and hallways. However, every configuration of buckling-restrained braced frame in eccentric configuration has a different seismic response in earthquake loadings. The effect of different parameters to the structural response of BRBF-E was studied such as eccentricity-to-length of bay ratio, cross sectional area of BRB, length of the bay, and location of the braces. Design parameters were investigated to determine its effects to the structural response of different eccentric configurations of BRBF-E with building height of 3, 6 and 9 stories. These parameters of BRBF-Es under seismic loading were analyzed using pushover analysis. The analysis of data was composed of comparison of inter-story drift and percentage failure of members. Comparing the different BRBF-E configurations, the single[1] brace configuration provides the most reduction in inter-story drift and percentage of failure of members. From the numerical experiment results, a design guide for BRBF-E was proposed.